El puerto marítimo de Cartagena y su importancia en el desarrollo económico de la región (2019)
For the decade of the eighties, the economic development models that are being implemented by the countries of the world, are not alien to the intention of Colombia, who will have to join this new challenge, with the implications in terms of road, customs and port infrastructure. This process will require to face the globalization and internationalization of the markets. In this sense, Colombia begins a process of restructuring its port policy, with the purpose of guaranteeing the tools that allow strengthening the internal port system and introducing the technologies required to make the sector a highly viable economically and competitive company in the transportation markets. and cargo logistics worldwide. Likewise, an investigation will be carried out applying three phases: starting from an initial phase of exploration, which will be carried out the consultation and review of the bibliographic material available in the entities or organizations related to the object of the investigation. A second phase of verification which will allow through interviews with the different actors of the local maritime and port sector, and officials of the entities or organizations related to the sector; and a final phase of analysis and results, in which the information obtained will be qualified, allowing this to solve the uncertainties raised in the formulation of the present research project